1992
DOI: 10.1002/ajpa.1330890104
|View full text |Cite
|
Sign up to set email alerts
|

Can we really walk straight?

Abstract: Twenty healthy men were asked to walk as straight as possible to a target 60 m away at normal speed. A series of footprints was recorded for each subject by having him wear socks soaked with red ink and walk on white paper fixed flat to the floor. Fourier analysis was applied to determine whether the subjects actually were able to walk straight, and the results revealed that all walked in a sinuous line rather than a straight line. Periodicity and amplitude of the meandering differed from subject to subject. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Nevertheless, biomedical asymmetries definitely play a role in veering [21,[24][25][26][27][28][29]. Scientific experiments were carried out in deserts and forests [30], or using previously seen targets [28][29][30][31][32][33][34][35]. Most of these experiments show an overlapping of scientific fields such as engineering, informatics, medicine or experimental psychology.…”
Section: Former Resultsmentioning
confidence: 99%
“…Nevertheless, biomedical asymmetries definitely play a role in veering [21,[24][25][26][27][28][29]. Scientific experiments were carried out in deserts and forests [30], or using previously seen targets [28][29][30][31][32][33][34][35]. Most of these experiments show an overlapping of scientific fields such as engineering, informatics, medicine or experimental psychology.…”
Section: Former Resultsmentioning
confidence: 99%
“…Many experiments have confirmed the tendency of people for deviating from the route. Uetake (1992) claimed that these gait asymmetries are caused by a small structural or functional imbalance of the limbs. Some researchers found the effect of the asymmetry on walking in a circle (Maus & Seyfarth, 2014) while others have not shown such correlations (Bestaven, Guillaud & Cazalets, 2012; Cratty, 1967; Souman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The studies on mechanisms behind the human ability to navigate also have concerned tests conducted among blind and healthy people in the absence of vision (Bestaven, Guillaud & Cazalets, 2012; Paquet et al, 2007; Souman et al, 2009). Human navigation has been examined based on walking tests in the absence of vision and hearing, to a previously seen goal at distances ranging from four m to 60 m (Commins et al, 2013; Day & Goins, 1997; Ellard & Shaughnessy, 2003; Israël et al, 2013; Loomis et al, 1992; Rieser et al, 1990; Thomson, 1983; Uetake, 1992) along a previously prepared track (straight, round and triangular). Other experiments concerned the movement of study participants straight ahead, at a given distance or within a specified time (Bestaven, Guillaud & Cazalets, 2012; Kallie, Legge & Schrater, 2002; Maus & Seyfarth, 2014; Paquet et al, 2007; Pollatou et al, 2009; Souman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Humans show tendencies for deviating from a given direction of movement, both to the left and to the right (Bestaven, Guillaud & Cazalets, 2012;Cratty, 1967;Kallie, Legge & Schrater 2002;Lenoir et al, 2006;Maus & Seyfarth, 2014;Pollatou et al, 2009;Rieser et al, 1990;Shapiro, 2015;Souman et al, 2009;Thomson, 1983;Uetake, 1992;Vuillerme, Nougier & Camicioli, 2002). Furthermore, Lenoir et al (2006) showed that the tendencies for turning left while running are more significant than when walking (tests carried out with vision).…”
Section: Discussionmentioning
confidence: 99%
“…The studies on mechanisms behind the human ability to navigate also have concerned tests conducted among blind and healthy people in the absence of vision (Bestaven, Guillaud & Cazalets, 2012;Paquet et al, 2007;Souman et al, 2009). Human navigation has been examined based on walking tests in the absence of vision and hearing, to a previously seen goal at distances ranging from 4 m to 60 m (Commins et al, 2013;Day & Goins, 1997;Ellard & Shaughnessy, 2003;Israël et al, 2013;Loomis et al, 1992;Rieser et al, 1990;Thomson, 1983;Uetake, 1992) along a previously prepared track (straight, round and triangular). Other experiments concerned the movement of study participants straight ahead, at a given distance or within a specified time (Bestaven, Guillaud & Cazalets, 2012;Kallie, Legge & Schrater, 2002;Maus & Seyfarth, 2014;Paquet et al, 2007;Pollatou et al, 2009;Souman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%